GREEN PATTERN CONCEPT FOR ROOFTOP LANDSCAPE ARCHITECTURE STUDY PROGRAM, TRISAKTI UNIVERSITY JAKARTA, INDONESIA - Reza Fauzi; Silia Yuslim (Journal of Synergy Landscape, 2021)
A garden is an outdoor relaxation area, set aside for the display of plants and other natural habitats solitary to human life. However, due to the reduced open space in urban areas, turning parks into gardens has become common. Therefore, a roof garden is an attractive option because it is private, and accessible to only certain people. Presently, the Study Program Landscape Architecture Universitas Trisakti, Jakarta, Indonesia, has a roof garden used to support certain subjects' practical activities.  However, the concept of a green pattern applied to the roof garden of this institution is not optimal. Therefore, this study aims to determine the design principles that have not been maximized in the roof garden of Study Program Landscape Architecture due to inaccuracy in the arrangement of the green pattern. This is descriptive research intended to describe and examine the characteristics, relationships, similarities, and differences of green patterns in the roof garden with other phenomena.